Pancreatic cancer screening in a clinical practice setting: it is the moment of Prevention - Adán-Merino, Luisa (2023)
Pancreatic cancer surveillance can improve outcomes in high-risk individuals. However, little is known about its applicability and findings in routine clinical practice. Our aim was to evaluate findings on screening tests in high-risk individuals in a clinical practice setting and to analyze factors associated with the presence of relevant pancreatic lesions. We developed a prospective observational study of pancreatic cancer high risk patients that meet criteria of surveillance from the International Cancer of the Pancreas Screening Consortium. The demographic variables, other risk factors and imaging findings are collected. Patients with significant findings are compared to those without noteworthy findings. Of 70 high-risk individuals, 25 fitted the criteria for pancreatic cancer surveillance. The most frequent condition was hereditary breast and ovarian cancer syndrome (60%). We identified eleven abnormal imaging findings (44%) and three of them (12%) were relevant: two intraductal papillary mucinous neoplasms and one localized pancreatic neoplasm. BRCA2 mutation was more frequent in patients with significant lesions (66.7% vs 30%, p=0.376) but smoking and diabetes were not associated with relevant findings (0 vs 18 %, p=0.578 and 0 vs 4.5%, p=0.880 respectively). Screening test could detect early-stage or resectable lesions in a significant in a significant percentage of the selected ings were in patients belonging to hereditary breast and ovarian cancer syndrome.